Parameterization and identification of the best-fit model for the soil water retention curve with multivariate analysis - Jessica Lima Viana; Aline Aparecida dos Santos; André Carlos Auler; Aaron Kinyu Hoshide; Karina Maria Vieira Cavalieri Polizeli; Jorge Luiz Moretti de Souza (Hydrological Sciences Journal, 2026)

A repeated measures cognitive affective bias test in rats: comparison with forced swim test - Benjamin Aliphon; Twain Dai; Jessica Moretti; Marissa Penrose-Menz; Wilhelmina H. A. M. Mulders; Dominique Blache; Jennifer Rodger (Psychopharmacology, 2023)

Insights into Blainville's beaked whale ( Mesoplodon densirostris ) echolocation ontogeny from recordings of mother‐calf pairs - Charlotte Dunn; Diane Claridge; John Durban; Jessica Shaffer; David Moretti; Peter Tyack; Luke Rendell (Marine Mammal Science, 2017)

Passive acoustic density estimation of sperm whales in the Tongue of the Ocean, Bahamas - Jessica A. W ard; Len Thomas; Susan Jarvis; Nancy DiMarzio; David Moretti; Tiago A. Marques; Charlotte Dunn; Diane C laridge; Eva Hartvig; Peter Tyack (Marine Mammal Science, 2012)
Long‐term passive acoustic monitoring of marine mammals on navy ranges provides the opportunity to better understand the potential impact of sonar on populations. The navy range in Tongue of the Ocean (TOTO), Bahamas contains extensive hydrophone arrays, potentially allowing estimation of the density of deep diving, vocally active species such as the sperm whale ( Physeter macrocephalus ). Previous visual surveys in TOTO have been of limited spatio–temporal coverage and resulted in only sporadic sightings of sperm whales, whereas passive acoustic observations suggest the species is present year round. However, until now the means of acoustically determining the specific number of individuals in each cluster has been limited. We used recently developed algorithms to identify the number of echolocating whales present during a 42 d study period. We screened a 297 h acoustic data set to determine the proportion of time animals were present; fifty 10 min samples during presence were analyzed to estimate the number of individuals vocalizing during each sample. These counts were combined with an independent estimate of the proportion of 10 min periods when tagged animals vocalize. The estimated average density was 0.16 whales/1,000 km 2 (CV 27%; 95% CI 0.095–0.264). The method is potentially applicable to other areas containing dense hydrophone arrays.

Changes in spatial and temporal distribution and vocal behavior of Blainville's beaked whales ( Mesoplodon densirostris) during multiship exercises with mid‐frequency sonar - Elena McCarthy; David Moretti; Len Thomas; Nancy DiMarzio; Ronald Morrissey; Susan Jarvis; Jessica Ward; Annamaria Izzi; Ashley Dilley (Marine Mammal Science, 2011)
The number and distribution of vocalizing groups of Blainville's beaked whales ( Mesoplodon densirostris ) were analyzed before, during, and after multiship mid‐frequency active sonar operations at the US Navy's Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. Groups of foraging animals were isolated by detecting their echolocation clicks using an array of bottom‐mounted hydrophones. Two data sets were evaluated consisting of 115 and 240 h of acoustic data in May 2007 and 2008, respectively. Vocal activity was observed to decline during active sonar exercises and increase upon cessation of sonar transmissions in both data sets. Vocal activity did not recover to preexposure levels in the postexposure time period in 2007 nor in the initial postexposure period in the 2008 data set. Clicks detected during sonar operations were generally found to be on the periphery of the hydrophone field and vocal durations declined for those groups that remained on the range in that time period. Receive levels were calculated for several vocal groups of whales and indicated that animals continued to forage when exposed to sonar at levels as high as 157 dB re: μPa.